Bioaccessibility and antioxidant activity of curcumin after encapsulated by nano and Pickering emulsion based on chitosan-tripolyphosphate nanoparticles. (November 2016) - Shah, Bakht Ramin; Zhang, Chunlan; Li, Yan; Li, Bin
Abstract: In the current study the influence of different lipid-based formulations (Pickering and nanoemulsions) and their droplet size on curcumin encapsulation and bioaccessibility, as well as on its anti-oxidant activity was investigated. Oil-in-water Pickering emulsion stabilized by chitosan-tripolyphosphate (CS-TPP) nanoparticles and nanoemulsions containing an organic phase (Span80:Tween80), were prepared with either medium chain triglyceride (MCT) or corn oil as long chain triglyceride (LCT). An in vitro gastrointestinal (GIT) model consisting of mouth, gastric and intestinal phases was used to characterize the rate and extent of lipid phase digestion of the ingested samples. A centrifugation method determined fraction of curcumin released into mixed micelles after digestion (bioaccessibility). These findings showed that after subjecting to simulated GIT model, all the emulsion systems experienced a progressive increase in mean particle size, due to droplet flocculation and coalescence after digestion. Electrical charge (ζ) of particles was observed to become highly negative as they passed through GIT due to accumulation of anionic bile salts, phospholipids and free fatty acids at their interfaces. The rate and extent of lipid digestion and bioaccessibility of curcumin increased with decreasing mean droplet diameter (NMCT > NCO > PMCT > PCO). Finally, we showed that as compared to free curcumin, the encapsulated curcumin showed higher radical scavenging activity (RSA), which confirmed the protective effect of the emulsion systems on the antioxidant activity of curcumin. Graphical abstract: Highlights: Curcumin encapsulated Pickering and nanoemulsions were prepared. Effects of oil and emulsion type on bioaccessibility of curcumin were evaluated. Radical scavenging activity of curcumin was enhanced by encapsulation.